A low-cost centimeter-level acoustic localization system without time synchronization. (January 2016) - Tan, Caiming; Zhu, Xinhua; Su, Yan; Wang, Yu; Wu, Zhiqiang; Gu, Dongbing
Highlights: It is an acoustic localization system which can be used indoors without time synchronization. The localization system is easily applied in most commercial off-the-shelf mobile devices. Good localization accuracy is achieved using only basic set of hardware. Abstract: In this paper, we present a range-based localization method without time synchronization. It uses only a speaker, a microphone, and some forms of device-to-device communication such as WIFI radio; thus, it is easily applied in most commercial off-the-shelf mobile devices such as cell phones. The localization scheme is composed of two stages. We obtain the initial distances between the moving object and the anchors in the first stage using a BeepBeep ranging system, in which they both send and receive sound signals. In the second stage, which is the main localization stage, the difference distances between the moving object and the anchors can be obtained using a OneBeep ranging system. Only the located object must emit sound signals periodically, and all of the anchors including the located object should receive the sound signals in the OneBeep system. The distances between the moving object and all the anchors can be obtained by adding the difference distances to the initial distances, and then, the moving object can be located. A localization experiment was conducted in a 6 × 9 m room with weak reflection, and the localization can reach centimeter-level accuracy in 5 min.